SO061SEX DIFFERENCES IN MORTALITY AMONG PEOPLE WITH END-STAGE KIDNEY DISEASE: DO WOMEN ALWAYS LIVE LONGER?. (6th June 2020) - De La Mata, Nicole; Macleod, Grace; Kelly, Patrick; Rosales, Brenda; Masson, Philip; Morton, Rachael; Webster, Angela
Abstract: Background and Aims: Female life expectancies consistently exceed males in the general population. Yet, this survival advantage may not persist in the presence of a chronic disease due to sex-based differences or healthcare inequities. We aimed to explore sex differences in survival among people with end-stage kidney disease (ESKD) compared to the general population. Method: We included the entire ESKD population in Australia, 1980-2013 and New Zealand, 1988-2012 from the Australian and New Zealand Dialysis and Transplant Registry. These were linked to national death registers to ascertain deaths and their causes. We estimated relative measures of survival, including standardized mortality ratios (SMR), cumulative relative survival and expected life years lost, using general population data (adjusting for country, age, sex and calendar year) to account for background mortality. Results: Of the 60, 823 ESKD patients, there were 25, 042 females (41%) and 35, 781 males (59%). Overall 34, 417 deaths occurred over the 368, 719 person-years of follow-up where a similar proportion of females (57%) and males (56%) died. While mortality sex differences within the ESKD population were minor, once compared to the general population female ESKD patients had greater excess deaths, worse relative survival and greater life years lost compared to male ESKD patients. Female ESKD patients had 12 times (SMR:11.5; 95%CI:11.3-11.7) and males had 7 times (SMR:6.7; 95%CI:6.7-6.8) the expected deaths, with the greatest sex disparity among younger ages and from cardiovascular disease. Relative survival was consistently lower in females (0.57, 95%CI:0.57-0.58 in males vs 0.54, 95%CI:0.54-0.55 in females at 5 years), where the excess mortality was 9% higher (95%CI:7-12%) in female ESKD patients (Fig 1A), adjusting for year and age. The average life years lost for female ESKD patients was 4-5 years greater than male ESKD patients (Average life years lost 25.9 years, 95%CI:25.1-26.7 in males and 31.4 years, 95%CI:30.5-32.1 in females aged 15 years at ESKD) (Fig 1B). Kidney transplantation reduced the sex differences in excess mortality, with similar relative survival (p=0.42; Fig 1C) and average life years lost reduced to 3-4 years for females (Fig 1D). Conclusion: The impact of ESKD is more profound for women than men with greater excess mortality, however kidney transplantation attenuates these differences. Our findings show that chronic diseases and sex can compound to produce worse outcomes where women lose their survival advantage in the presence of ESKD.